Maternal country of birth and in-hospital exclusive breastfeeding: results from a Portuguese study. (13th November 2019) - Lisi, C; Freitas, C; Barros, H
Abstract: Background: Breastfeeding provides benefits for children, mothers, society and the environment. The promotion of optimal breastfeeding, from an early stage in life is, therefore, a public health priority. Infant feeding can be influenced by maternal country of birth. However, studies carried out in European settings point to inconsistent findings. This study aims to compare first day in-hospital exclusive breastfeeding among migrant and native women in Portugal. Methods: This study is based on a national project on perinatal health among migrants and natives in Portugal (baMBINO). Out of 39 public maternity units in mainland Portugal, 32 were enrolled. Women aged 18 years old or older with a live birth were recruited. The final sample included 5109 participants (2431 natives and 2678 migrants). Logistic regression was used to assess the association between maternal country of birth and in-hospital exclusive breastfeeding. Results: Migrant participants included women from Portuguese-speaking African countries (PSAC) (49, 7%), Brazil (18%), Eastern Europe (10.2%), other European countries (9.6%), Asia (5.5%) and other countries (7.0%). No differences were found between migrants and natives, with the exception of women from PSAC who were more likely to exclusively breastfeed during the first day of hospital stay (aOR 1.34 CI95% 1.05-1.72), irrespective of maternal age, education, parity, type of pregnancy, reproductive assistance, tobacco use, gestational age, newborn birth weight, mode of delivery and antenatal care. Conclusions: In Portugal, women from PSAC are more likely to exclusively breastfeed their babies during the first day of hospital stay when compared to native women. Strategies to maintain healthy breastfeeding practices in this population are fundamental. Key messages: Women from PSAC are more likely to breastfeed exclusively in the first day after delivery than Portuguese natives. They should be supported in the maintenance of optimal breastfeeding practices.